The property lobby : the hidden reality behind the housing crisis - Colenutt, Bob (Policy Press, 2020)
The complex and self-serving nexus behind the UK's housing crisis is laid bare in this passionate book from Bob Colenutt. Investigating the network of landowners, house-builders, financial backers and politicians, he reveals how we have been forced to accept the cycle of low supply and high prices, and proposes solutions to the housing emergency.